Evaluating the Effectiveness of School-Based Feeding Program in Secondary Schools in Cordon, Isabela - Pinapit, Lizabeth (Studies in Technology and Education, 2026)
This descriptive-evaluative study aimed to evaluate the effectiveness of the school-Based Feeding Program in Secondary Schools in Cordon, Isabela. The respondents of the study were 50 stakeholders and 84 student beneficiaries from Grade 8 and Grade 9 who took part in the feeding program during the school year 2025-2026. This study used descriptive statistics such as frequency, percentage, and weighted mean to describe the data. It also used inferential statistics like chi-square, t-test, and ANOVA to find out if there were significant differences when the respondents were grouped according to their profile variables. The results of the study showed that the respondents believed the feeding program still needed improvement to maintain its effectiveness for the beneficiaries in secondary schools. The coordinators and students reported only slight improvements in school attendance, participation, and academic performance. The factors that supported the feeding program, such as financial and stakeholder support, were only at a moderate level. The school-based feeding program experienced challenges including problems with human resources, lack of stakeholder engagement, insufficient funding, and issues in student participation. These challenges affected the sustainability of the feeding program. Furthermore, there was a noticeable improvement in the nutritional condition of severely wasted and wasted students after they joined the feeding program. On the other hand, there were significant differences found in the respondents’ profile based on their perception and experiences with the feeding program. The researcher recommended that to make the feeding programs in secondary schools in Cordon, Isabela more effective, the schools should continue improving their meal planning, regularly monitor the students’ nutritional status, maintain the school garden, and encourage active participation among students. Lastly, addressing financial and other resource-related challenges, as well building strong partnerships with the schools, the local government unit, and other stakeholders, are essential to sustain the implementation of the feeding program. Keywords: School-based feeding program, program effectiveness, supports, challenges, nutritional status